(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Compression of the optic nerve/chiasm complex is typical for patients with basal neoplasms located in the middle or anterior cranial fossae. The most common of these neoplasms are pituitary adenomas, meningiomas and craniopharyngiomas. Chiasmal compression is accompanied by a gradual decrease in visual acuity, bitemporal visual field defects and development of primary descending optic atrophy (OA). Optical coherence tomography (OCT) is a relatively new non-invasive imaging modality that allows objective assessment of stereometric parameters of the optic nerve. Purpose: To assess OCT-measured morphostructural parameters of the retina and optic nerve in patients with primary optic atrophy due to compression by basal brain tumors (BBT). Material and Methods: This retrospective study included the records of 43 patients (86 eyes) who received treatment for BBT at the Romodanov Institute during 2016 to 2017. Patients underwent clinical and neurological, eye, and otoneurological examination, and neuroimaging procedures, particularly OCT with a Revo NX instrument (Optopol Technology SA, Poland). Results: The OCT features of compressive descending OA varied with the severity of chiasmal syndrome (CS). The peripapillary retinal nerve fiber layer (RNFL) thickness was statistically significantly different between patients with CS versus controls and versus patients with no CS. In addition, there was a significant difference (p < 0.05) in reduction in neuroretinal rim area in patients with CS, compared with controls. The macular ganglion cell complex (GCC) thickness was thinner in each subgroup of patients than in the control group. There were significant direct correlations of visual field mean deviation (MD) with RNFL thickness and GCC thickness. Conclusion: OCT is a modern non-invasive objective modality that can be utilized in the diagnosis of primary OA, and allows quantifying the reduction in nerve fiber thickness. The GCC thickness analysis provides earlier diagnosis of chiasmal compression than identification of temporal visual field defects or analysis of peripapillar RNFL thickness.